Effects of aqueous extract of prismatomeris glabra root on non-spatial memory in rats using object discrimination test - Norazrina Azmi,; Wei-Theng Loh,; Siti Suriani Omar,; Juriyati,; Aishah Adam, (Universiti Kebangsaan Malaysia, 2011)
The aqueous extract of Prismatomeris glabra root has been used traditionally in Malaysia by the aborigines and certain rural Malays for its ergogenic effects, to maintain wellness and to enhance physical stamina. It has also been used as an aphrodisiac for generations in the east coast of Peninsular Malaysia. Previous studies have shown that plants with ergogenic effects may also act as a stimulant and impair cognitive function. Therefore, we seek to investigate the effects of P. glabra on non-spatial memory in male Sprague Dawley rats using object recognition test. Trial rats were injected intraperitoneally with an aqueous extract of P. glabra roots at doses of 50 and 100 mg/kg for the acute (30 min) and subacute (7 days) studies. Scopolamine (0.3 mg/kg) was used as a positive control only in the acute study meanwhile control rats were injected with saline. The locomotor activity of rats was also determined in the same test. We demonstrated that groups treated with 50 and 100 mg/kg of the extract lost their ability to discriminate the novel from familiar object in choice phase and did not alter the locomotor activity in both studies. Our results also indicated that the deficits in non-spatial working memory occured at these doses were not due to impaired locomotor activity.